Prehospital procedures and transport of the diseased with a suspected Chronic Obstructive Pulmonary Disease - case description - Bartosz Wydrych; Justyna Wydrych; Krzysztof Kwiecień; Paulina Dobrawa Zięba-Szczepaniak; Grażyna Nowak-Starz (Kazimierz Wielki University, 2019)
Chronic iterative lung disease is an incurable disease that can be prevented. Available treatment, including cessation of smoking, allows the hindering of its progress. The goal of COPD treatment is to alleviate its symptoms, improve effort tolerance as well as the quality of life, and reduce the risk of progression by reducing the number of exacerbations. Medical Emergency Unit in Kielce accepted a call regarding a 55-year-old man who complains about severe shortness of breath for several hours, not responding to the medicines he has at home. The Basic Emergency Response Team is dispatched to the event In practice, emergency medical team interventions regarding patients reporting dyspnea are not uncommon. In a significant proportion of patients, dyspnea occurs as a result of a chronic obstructive pulmonary disease (COPD).